(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of high body mass index in ovarian cancer and to compare the stage of tumour in patients of ovarian cancers with normal versus high BMI. Study Design: Descriptive, cross-sectional Place and Duration of Study: This study was conducted at the Department of Pathology, King Edward Medical University, Lahore from September 2017 to March 2018. Materials and Methods: One hundred and fourteen patients having ovarian cancer of age 15-55 years were included. Patients having metastatic ovarian carcinoma were excluded. Frequency of high BMI was recorded and two groups (A & B) were formed according to their BMI i.e. body mass index BMI ≥30 kg/m2 and body mass index BMI <30 kg/m2. Tumor stage of these cases was assessed by FIGO staging system. Results: Mean age was 38.89±10.07 years. Most of the females, i.e. 66 (57.89%) were between 46 to 55 years of age. Mean duration of ovarian cancer was 9.12±3.68 months. Out of the 114 patients, 99 (86.84%) were married and 15 (13.16%) were unmarried. Frequency of high body mass index in ovarian cancer was found in 35 (30.70%) patients, whereas there was normal BMI in 79 (69.30%) patients. Conclusion: Frequency of high body mass index in ovarian cancer is quite high. No statistically significant difference was noticed in stage of tumour in patients with normal versus high BMI.